Cell saver processing mitigates the negative effects of wound blood on platelet function. Issue 7 (3rd May 2016) - Gäbel, J.; Malm, C. J.; Radulovic, V.; Shams Hakimi, C.; Westerberg, M.; Jeppsson, A.
Abstract : Background: Wound blood is highly activated and has poor haemostatic properties. Recent data suggest that retransfusion of unwashed wound blood may impair haemostasis. We hypothesized that cell saver processing of wound blood before retransfusion reduces the negative effects. Methods: Wound blood was collected from 16 cardiac surgery patients during cardiopulmonary bypass. One portion of the wound blood was processed in a cell saver and one portion left unprocessed. Increasing amounts of unprocessed blood (10% and 20% of the systemic blood volume) or corresponding volumes of processed blood were added ex vivo to whole blood samples from the same patient. Clot formation was assessed by modified thromboelastometry (ROTEM ® ) and platelet function with impedance aggregometry (Multiplate ® ). Results: Addition of unprocessed wound blood significantly impaired clot formation and platelet aggregability. Cell saver processing before addition did not influence clot formation but abolished completely the negative effects of wound blood on platelet aggregability tested with all agonists. Median adenosine diphosphate‐induced platelet aggregation was 51 (25th and 75th percentiles 42–69) when 20% processed cardiotomy suction blood was added vs. 34 (24–52) U when 20% unprocessed blood was added, P < 0.001. The corresponding figures for arachidonic acid‐, thrombin receptor activating peptide‐ and collagen‐induced aggregation was 21 (17–51) vs. 13 (10–25) U, 112 (87–128) vs. 78 (65–103) U and 58 (50–73) vs. 33 (28–44) U, respectively, all P < 0.001). Conclusion: The results suggest that cell saver processing before retransfusion mitigates the negative effects of wound blood on platelet function despite that cell saver processing reduces platelet count.